2021
DOI: 10.1111/desc.13116
|View full text |Cite
|
Sign up to set email alerts
|

Representing agents, patients, goals and instruments in causative events: A cross‐linguistic investigation of early language and cognition

Abstract: Although it is widely assumed that the linguistic description of events is based on a structured representation of event components at the perceptual/conceptual level, little empirical work has tested this assumption directly. Here, we test the connection between language and perception/cognition cross-linguistically, focusing on the relative salience of causative event components in language and cognition. We draw on evidence from preschoolers speaking English or Turkish. In a picture description task, Turkis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
(160 reference statements)
1
7
0
Order By: Relevance
“…When people view events, there is a strong tendency to fixate earlier on the agent than the patient (7,8,28). This agent bias also manifests itself in higher accuracy for agents when scanning stimuli very rapidly [<100 ms; (29)(30)(31)], when remembering events (32), or when detecting small changes between events (33). Indeed, the bias might be part of core cognition (34) in humans, attested early on in infants (13), and inscribed into fundamental mechanisms of event processing (8,28).…”
Section: Event Cognition In Humansmentioning
confidence: 99%
“…When people view events, there is a strong tendency to fixate earlier on the agent than the patient (7,8,28). This agent bias also manifests itself in higher accuracy for agents when scanning stimuli very rapidly [<100 ms; (29)(30)(31)], when remembering events (32), or when detecting small changes between events (33). Indeed, the bias might be part of core cognition (34) in humans, attested early on in infants (13), and inscribed into fundamental mechanisms of event processing (8,28).…”
Section: Event Cognition In Humansmentioning
confidence: 99%
“…One source of evidence is behavior in tasks probing event cognition. For example, change‐detection studies have demonstrated a conceptual asymmetry between Goals and Sources (Lakusta & Landau, 2012 ; Regier & Zheng, 2007 ) and between Goals and Instruments (Ünal et al., 2021 ). Individuals that constitute more prototypical agents given linguistic diagnostics have been shown to be more prototypical agents in nonlinguistic categorization tasks (Rissman & Lupyan, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…When viewing events, English‐speaking adults are also slower to recognize instruments than agents, patients, or goals, as revealed through patterns of eye‐gaze (Wilson, Papafragou, Bunger, & Trueswell, 2011 ). In addition, both English‐ and Turkish‐learning children are less likely to notice changes to an instrument than to a patient or goal in a change‐detection task (Ünal, Richards, Trueswell, & Papafragou, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the theory that these roles are part of core cognition, there may be a single set of categories underlying both linguistic and conceptual processes. The view that event roles are tightly linked across semantic and conceptual domains is supported by studies investigating thematic role hierarchies (Grimshaw, 1990; Levin & Rappaport-Hovav, 2005; Ünal et al, 2021). For example, adults across a range of languages are more likely to mention Goals than Sources when describing motion events (Lakusta & Landau, 2005, 2012; Narasimhan et al, 2012; Papafragou, 2010).…”
Section: Do Linguistic and Conceptual Role Categories Share Similar S...mentioning
confidence: 99%